Advances in Italian Mechanism Science Proceedings of the First International Conference of IFToMM Italy - Boschetti, Giovanni; Gasparetto, Alessandro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This volume contains the Proceedings of the First International Conference of IFToMM Italy (IFIT2016), held at the University of Padova, Vicenza, Italy, on December 1-2, 2016. The book contains contributions on the latest advances on Mechanism and Machine Science. The fifty-nine papers deal with such topics as biomechanical engineering, history of mechanism and machine science, linkages and mechanical controls, multi-body dynamics, reliability, robotics and mechatronics, transportation machinery, tribology, and vibrations.
system, by Giuseppe Bucca, Andrea Collina and Ezio Tanzi -- Part IX Vibrations -- Low-cost Experimental Assessment of Forces in the Contact Bridge-Soundboard of Stringed Musical Instruments, by Enrico Ravina -- Vibration Modes of PiezoelectricBimorphs: a Sensitivity Analysis, by Alberto Borboni, Cinzia Amici, Valter Cappellini and Rodolfo Faglia -- Concurrent Active Control and Dynamic Structural Modification in the Design and the Optimization of Vibrating Systems, by Dario Richiedei, Roberto Belotti and Roberto Caracciolo -- A vibration isolator based on magneto-rheological elastomer, by Renato Brancati, Giandomenico Di Massa and Stefano Pagano -- A Numerical-Analytical Model for the Study of the Elasto Kinematic Behavior of a Macpherson Suspension, by Francesco Timpone -- A smart system for shock and vibration isolation of sensitive electronic devices on-board a vehicle, by Stefano Pagano, Salvatore Strano, Giandomenico Di Massa, Marco De Michele, Giovanni Pisani, Giuseppe Frisella and Sergio Lippolis -- Wavelet analysis of Gear rattle induced by a multi-harmonic excitation, by Renato Brancati, Ernesto Rocca, Sergio Savino and Francesco Timpone -- Special Session in honor of prof. Aldo Rossi for his 70th birthday Chairman: prof. Carlo Ugo Galletti -- Analytical and Multibody Modelling of a Quick-Release Hook Mechanism, by Luca Bruzzone, Davide Bonatti, Giovanni Berselli and Pietro Fanghella -- Evolution of a Dynamic Model for Flexible Multibody Systems, by Paolo Boscariol, Paolo Gallina, Alessandro Gasparetto, Marco Giovagnoni, Lorenzo Scalera and Renato Vidoni -- Anti-Hedonistic Mechatronic Systems, by Lorenzo Scalera, Paolo Gallina, Alessandro Gasparetto and Marco Giovagnoni -- On the use of cable-driven robots in early inpatient stroke Rehabilitation, by Giulio Rosati, Stefano Masiero and Aldo Rossi. .
Keywords: Mechanical engineering; Mechanics, Applied; Control engineering; Robotics; Automation; Mechatronics; Industrial engineering; Production engineering; Mechanical Engineering; Engineering Mechanics; Control, Robotics, Automation; Mechatronics; Industrial and Production Engineering